Effect of Plant Preservative Mixture Ppmtm on the Shoot Regeneration of Watercress (Nasturtium Officinale) - Faizy, Hadar S.; AL-Zubaydi, Sami R.; Nair, Muraleedharan (Science Journal of University of Zakho, 2017)
Plant Preservative Mixture™ (PPM), a relatively new broad-spectrum preservative and biocide for use in plant tissue culture, was evaluated as an alternative to the use of conventional antibiotics and fungicides in plant tissue culture. Culture inoculated in MS media supplemented with PPM (1.5 ml/l) was the effective concentration which gave the best values. The top values were recorded for all studied characters using apical buds compared with lateral buds. The combination between apical buds and (1.5 ml/l ) PPM concentration showed the superior values of all studied parameters( 33.25%,19.40%, 14.46%,20.53% and 79.46%)(60.55%,39.80%,20.97%,45.33% and 54.44%) and (31.20%, 20. 06%, 12.33%, 35.13% and 81.06 %) for contamination, %bacterial contamination, % offungi contamination, dead explants% and survival explants% respectively.  Different concentrations of PPM (0, 0.5, 1.0, 1.5, 2.0 and 2.5 ml/l) were tested using single node and apex explants of watercress (Nasturtium officinale). PPM at (1.5ml/l)  had significant effect on the studied characters; shoots height, shoots number, leaf pairs number, fresh and dry weight which they reaches (4.16, 4.62, 42.00,0.524 and 0.063 g, respectively ). Apex bud explants showed the greatest effect on shoots height shoots number, leaf pairs number, fresh and dry weight and their values were 3.52, 32.02, 3.38, 0.405 and 0.036 g, respectively. The best parameter were recorded on MS media supplemented with PPM at (1.5ml/l) with apex buds explant  (4.55, 5.34, 46.28, 0.570 and 0.085, respectively) for shoots height, shoots  number, leaf pair number, fresh and dry weight. Current study aimed to determine the best concentration of PPM for limiting the contamination of watercress and micro shoot regeneration.
Keywords: Nasturtium officinale; PPMTM; Contamination; Antibiotic